Characterization of Fuel Types for the Canadian Region Using MODIS MCD12Q1 Data - Enrica Nestola; Olga Gavrichkova; Vito Vitale; Enrico Brugnoli; Maurizio Sarti (Fire)
The characterization and mapping of fuel types is one of the most important factors to consider in the development of accurate fire behavior models. This study introduces a new methodology for generating a fuel map that can be easily updated on an annual basis. The method involves identifying associations between the Moderate Resolution Imaging Spectroradiometer (MODIS) land cover MCD12Q1 classes and the fuel-type classes categorized by the Canadian Fire Behavior Prediction System (FBP). For this purpose, MCD12Q1 Land Cover Type 1 data (MODIS LCM) were collected for the Canadian region. Concurrently, the Canadian fuel-type map implemented in the Fire Behavior Prediction System (FBP FTM) served as the reference dataset. Both MODIS LCM and FBP FTM were reclassified into a new Canadian FTM (NC-FTM) based on seven fuel-type classes. The method involves three key steps: (1) adapting MODIS LCM and FBP FTM for the classification of the Canadian region, (2) removing ambiguity, and (3) characterizing and assessing the accuracy of the new fuel-type classification using a confusion matrix classification algorithm. The achieved accuracy for the new classification exceeds 85%, highlighting the effectiveness of the approach. The use of MODIS LCM offers a cost-effective method for the annual characterization and mapping of fuel types, providing a practical improvement to the FBP model for Canada. Furthermore, with the proposed methodology, a fuel-type map can be generated for other specific areas of interest in the boreal region.